Language Control in Different Contexts: The Behavioral Ecology of Bilingual Speakers - Green, David W. (Frontiers in Psychology, 2011)
This paper proposes that different experimental contexts (single or dual language contexts) permit different neural loci at which words in the target language can be selected. However, in order to develop a fuller understanding of the neural circuit mediating language control we need to consider the community context in which bilingual speakers typically use their two languages (the behavioural ecology of bilingual speakers). The contrast between speakers from code-switching and non-code switching communities offers a way to increase our understanding of the cortical, subcortical and, in particular, cerebellar structures involved in language control. It will also help us identify the non-verbal behavioural correlates associated with these control processes.